2014
DOI: 10.1021/om500182p
|View full text |Cite
|
Sign up to set email alerts
|

Lithiation of Chromium and Tungsten Aminocarbene Complexes: An Easy Approach to Functionalized Aminocarbene Complexes

Abstract: Thiophene-and furan-derived aminocarbene complexes are regioselectively lithiated by BuLi at position 5, while lithiated aminocarbenes containing pyrrole or phenyl groups can be obtained by a bromine to lithium exchange reaction using BuLi. Such prepared lithiated aminocarbene complexes react with alkyl halides, aldehydes, ketones, acyl chlorides, and DMF, giving high yields of functionalized aminocarbene complexes hardly accessible by other ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Recently, we have observed that heterocyclic aminocarbene complexes 1a – d can be smoothly lithiated using BuLi at −78 °C. The formed lithiated carbenes 2a – d can be alkylated by primary alkyl halides and/or transformed to secondary and tertiary alcohols by the reaction with aldehydes or ketones, or acylated giving ketones . The feasibility of the lithiation of 1a – d led us to explore the potential of these lithiated carbene complexes in Negishi cross-coupling reactions (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have observed that heterocyclic aminocarbene complexes 1a – d can be smoothly lithiated using BuLi at −78 °C. The formed lithiated carbenes 2a – d can be alkylated by primary alkyl halides and/or transformed to secondary and tertiary alcohols by the reaction with aldehydes or ketones, or acylated giving ketones . The feasibility of the lithiation of 1a – d led us to explore the potential of these lithiated carbene complexes in Negishi cross-coupling reactions (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the tendency of alkoxycarbene complexes to add organolithiums, only aminocarbene complexes can be successfully metalated . Thus, chromium aminocarbene complexes 1a – d were lithiated with BuLi and, after transmetalation with ZnBr 2 , subjected to Pd­(PPh 3 ) 4 -catalyzed coupling with a thiophene-derived bromoethoxycarbene complex of chromium 2a (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 92%
“…The solvents were dried and degassed by standard procedures; silica gel (Merck, Geduran Si 60, 63–200 μm) was used for column chromatography. Pentacarbonyl­[( N , N -dimethylamino)­(2-thienyl)­carbene]­chromium­(0) ( 1a ), pentacarbonyl­[( N , N -dimethylamino)­(2-furyl)­carbene]­chromium­(0) ( 1b ), pentacarbonyl­[( N , N -dimethylamino)­(5-bromo-1-methyl-2-pyrrolyl)­carbene]­chromium­(0) ( 1c ), pentacarbonyl­[( N , N -dimethylamino)­(4-bromophenyl)­carbene]­chromium­(0) ( 1d ), pentacarbonyl­[ethoxy­(5-bromo-2-thienyl)­methylene]­chromium(0) ( 2a ), and pentacarbonyl­[ethoxy­(5-bromo-2-thienyl)­methylene]­tungsten(0) ( 2b ) were prepared by the reported procedures; other compounds were purchased.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A c c e p t e d M a n u s c r i p t 83 Successful arylithium formation in the presence of aminocarbene complex functionality (e.g. formation of lithiothiophene 611 in Scheme 44) was achieved [938]. Heteroaryl substituted aminocarbene complexes (e.g.…”
Section: F Reactions Involving the Transfer Of A Fischer Carbene Unimentioning
confidence: 99%